Afecciones que persisten: memoria episódica y ética animal - Corda, Gabriel (2024)
Based on a naturalistic philosophical methodology, this article proposes two features of episodic memory that are relevant for thinking about some issues in animal ethics: (1) the reconstructive character of affectively charged past events, and (2) the narrative character and autonoethical awareness of episodic memory. Regarding the first issue, we briefly review the current debate over evidence that some animals have internally triggered experiences of hedonic valence and suffer from post-traumatic stress disorder. We then explore some of the implications of this trait for animal welfare in intensive production systems. Next, we review the debate on the second issue and demonstrate the role that the properties of episodic memory have played in the attribution of personhood in the philosophical tradition, along with more deflated conceptions of these capacities, understood as a psychological unity or continuity. The final section argues that these contemporary conceptions, which link certain features of memory to psychological unity, allow for the attribution of personhood to nonhuman animals.